Kinematic evolution of the Pieniny Klippen Belt in Cenozoic (Ukrainian Carpathians) - A. V. Murovskaya; M. V. Nakapelyukh; Yu. M. Vikhot; V. E. Shlapinskiy; I. N. Bubnyak; S. V. Mychak (Геофизический журнал, 2016)
The data on surface, subsurface and deep structure of the Pieniny Klippen Belt (PKB) have been summarized and new results of its geological-structural and fault kinematic studies within the Ukrainian part of the Eastern Carpathians have been presented. In its contemporary appearance as a narrow strongly tectonized zone between the Outer Carpathians and Trans-Carpathian trough PKB was formed in Oligocene—Miocene in the place of ancient ocean. On the surface it is situated within the rootless Pieniny nappe and in the deep it is a steeply dipping deformation zone which developed under compression, simple dextral strike-slip, transtension and transpression. Mesostructures of horizontal shortening and vertical elongation, thrusts and thrust-related folds as well as structures of lateral extrusion — dextral strike-slip along sub-meridional slicken-sides correspond to SW—NE 220° trending compression and correlate with the stage of Alcapa microplate progression in NE direction in Oligocene—Early Miocene. In Early Miocene as a result of counter-clockwork rotation of Alcapa dextral strike-slip deformation is concentrated in boundary zone between Alcapa and accretionary prism of Ukrainian Flysch Carpathians. The stress fields of strike-slip type with orientation of compression axis SE 165—SW 215° and its “rotation” in a zone of simple shear correspond to this stage. Present deformation regime is characterized as transpressure with SW—NE orientation of compression axis.